(untitled) (World Economics and Finance Bulletin, 2022)
Nowadays, tennis and technology are so advanced that there are no areas left without penetration, no occupied walls. Of course, it has also entered the field of Economics and we have discovered a new economy. We call this economy the digital economy. In the latter times, the concept of "digital economy" is used many times. In fact, in many developed countries, the digital economy has significantly influenced the factors of their development. In the life of society, the digital economy plays an important role. In this article, opinions and comments will be made about the concept of the digital economy and its level and stages of development in our country.